An eye-tracking study of reading long and short novel and lexicalized compound words - Jukka Hyönä; Alexander Pollatsek; Minna Koski; Henri Olkoniemi (Bern Open Publishing, 2020)
An eye-tracking experiment examined the recognition of novel and lexicalized compound words during sentence reading. The frequency of the head noun in modifier-head compound words was manipulated to tap into the degree of compositional processing. This was done separately for long (12-16 letter) and short (7-9 letters) compound words. Based on the dual-route race model (Pollatsek et al., 2000) and the visual acuity principle (Bertram & Hyönä, 2003), long lexicalized and novel compound words were predicted to be processed via the decomposition route and short lexicalized compound words via the holistic route. Gaze duration and selective regression-path duration demonstrated a constituent frequency effect of similar size for long lexicalized and novel compound words. For short compound words the constituent frequency effect was negligible for lexicalized words but robust for novel words. The results are consistent with the visual acuity principle that assumes long novel compound words to be recognized via the decomposition route and short lexicalized compound words via the holistic route.